Studi Kenyamanan termal dan konsentrasi CO2 pada kamar anak ber-pendingin udara masa Pandemi Covid-19 - Sahabuddin Latif; Andi Syahriyunita Syahruddin; Sri Wahyuni (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
The government's implementation of online learning for students during the Covid-19 pandemic since March 2019 has impacted thermal comfort and CO2 concentration in the rooms where children engage in activities at home. This study aims to investigate the thermal comfort and CO2 concentration in air-conditioned children's rooms during the Covid-19 pandemic. The research method was carried out through field measurements consisting of collecting external climate data, internal room data, and CO2 concentration levels. Temperature, air humidity, and CO2 concentration levels were recorded every minute for four days. In addition, surface temperatures of the floor, ceiling, and walls were recorded every 15 minutes between 06:00-18:00 Central Indonesia Time (CIT). The results showed that the average room air temperature was 26.2 °C, with the AC thermostat set at 26 °C. However, uneven air distribution was caused by the furniture arrangement that hindered uniform air distribution. CO2 concentration levels increased above the normal limit when more than three people were in the room, especially at night. To quickly reduce CO2 levels to meet the standards, it is recommended to open windows or doors to facilitate air circulation.